USING AN ANISOTROPIC GYROTROPIC MODEL FOR ESTIMATING GYRATION AND ATTENUATION CONSTANTS - Chichinina T.; Obolentseva I. (My University, 2003)
A new approach to estimating of shear-wave attenuation is proposed. The method is based on an assumption that an anisotropic attenuating geological medium possesses gyrotropic properties. Doing so allows to obtain attenuation constant together with gyrotropic constant. Some examples of experimental determination of gyration and attenuation constants are given. A presentation of the new way of determining shear-wave attenuation constant is proceeded by a brief elucidation of the main aspects of the phenomenological theory of gyrotropy. The most interesting and important phenomenon inherent to gyrotropy—rotation of shear-wave polarization plane—is illustrated.
Keywords: Gyrotropy; Anisotropy; Attenuation; Polarization